Efektifitas Akupresur Titik BL 32 Dan Li 4 Terhadap Tingkat Nyeri Persalinan Kala I Fase Aktif Primigravida - Wahyuni, Sri; Setiawandari, Setiawandari; Waroh, Yuni Khoirul (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2024)
Labor pain is a physiological process, but if not managed properly it can cause side effects of labor such as secondary arrest. Acupressure is a non-pharmacological therapy that is effective in reducing problems faced by mothers giving birth, especially primigravida. The purpose of this study was to determine the effectiveness of acupressure points BL 23 and Li 4 on the level of labor pain in the first stage of the active phase of primigravida. The type of research is quasi-experimental with a one group pre-test post-test design. The sample size was 39 mothers giving birth in the first stage of the active phase, taken by accidental sampling from the population of primigravida mothers giving birth in January-March 2024. Measurement of labor pain levels using the Numerical Ranting Scale. The results of the study showed that the average pre-test pain level was 7.23 with a maximum scale of 9, while the average post-test labor pain level was 2.79 with a maximum scale of 6. The Wilcoxon Signed Ranks test results were ρ = 0.00, which means that acupressure points BL 32 and Li 4 have an effect on the level of labor pain, so it can be concluded that the acupressure method of points BL 32 and Li 4 is effective for the level of labor pain in the first active phase of primigravida. Suggestions for acupressure points BL 32 and Li 4 can be applied as a non-pharmacological method to reduce the level of labor pain in the first active phase in basic health services because it is easy, cheap and effective.